Molecular Characterisation of Infectious Bursal Disease Virus Isolated in Iran for Development of an Enzyme-Linked Immunosorbent Assay Based on Recombinant VPX Protein - Hosseini, Seyed Davood (2005)
The acute form of infectious bursal disease (IBD) is considered as an economically significant disease among the poultry diseases reported in Iran. It was first reported as being caused by very virulent IBD virus (IBDV) based on conventional methods. Infectious bursal disease outbreaks are still being reported frequently, in spite of vaccination and sanitation measures which are the routine practices for the control of IBD in the country. Since there was no report available on the molecular characteristics of IBDV based on segment A in Iran, which is necessary for the establishment of proper control measures, it was important to characterise the antigenic and virulent properties of the strains prevalent in Iran.